Post traumatic stress and anxiety in patients with acute coronary syndrome - Atik, Derya; Neşe, Adile; Çakır, Meral; Ünal, Ahmet; Yüce, Ulviye Özcan (International Journal of Research in Medical Sciences, 2017)
Background: Acute coronary syndrome (ACS) is one of the diseases in which psychiatric complications develop, with initiation of treatment, and having cardiac, patient-specific behavioral problems. The aim of this study was to investigate symptoms of posttraumatic stress disorder (PTSD) and anxiety in patients that experience ACS. The relationship between PTSD symptoms and anxiety and the relationship between these psychological conditions and certain personal characteristics were reviewed. Methods: In this study, which was prospective and descriptive, 215 patients who experienced ACS were evaluated in the first month after ACS. The data in the research was collected using the Patient Identification Form, Posttraumatic Stress Disorder Symptoms Scale Self-Report (PSS-SR) and Spielberg State-Trait Anxiety Inventory (STAI-T). Results: 70.2% of the patients were male and 31.2% were retired. The PSS-SR mean score was 28.40 ± 10.42 and the mean STAI-T score was 57.65 ± 12:37. Between the STAI and PSS-SR there was a statistically significant positive correlation. In women, workers, grade 1 obese patients, those using alcohol, and those with chronic disease the average PSS-SR scores were significantly higher. Housewives, illiterate individuals and 1st degree obese patients had a higher average score of anxiety, as well as patients with chronic diseases and higher alcohol use.